Manajemen Sarana Prasarana Dalam Mencapai Tujuan Pendidikan Anak Usia Dini - Makmur Syukri; Fachruddin Azmi; Riswan Berutu; Muhammad Ridho Al-Fattah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to find out how the management of facilities and infrastructure is in achieving the goals of early childhood education. Facilities and infrastructure is a tool that has a very important role in a process in order to achieve success and achievement in the end result. The research method used in this study is the research library method.